Effectiveness of Manual Myofascial Release versus Instrument assisted soft tissue Mobilization (IASTM) in patients with chronic neck pain - RCT - Zoha Sabir; Sana Bashir; Qurat ul Ain Saeed; Sameera Gul; Syeda Sumaira Batool (Journal Riphah College of Rehabilitation Sciences)
Background: Chronic neck pain, affecting nearly 50% of the global population annually, is a significant global burden. While Instrument Assisted Soft-tissue Mobilization (IASTM) has shown effectiveness in treating musculoskeletal injuries, there is a scarcity of evidence comparing it with Manual Myofascial Release (MMFR).